Model characteristics of special physical fitness in elite high jumping sport - Latypov, I. K.; Sirotkin, D. G. (Theory and Practice of Physical Culture, 2019)
Integrated progress tests are in high priority in the modern training systems in the high jumping sport. The study was intended to develop and test by an experiment a new progress test model with model characteristics of special physical fitness applicable at the sport excellence stage in elite high jumping sport. The study included a questionnaire survey of athletes, the physical fitness progress tests and mathematical processing of the test data, with 38 elite high jumpers (qualified CMS to WCMS) sampled for the study.